2004
DOI: 10.1177/1470595804041524
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Diverse National Values on Strategic Investment Decisions in the Context of Globalization

Abstract: This study examines the effect of diverse national values on strategic investment decision (SID) making in the context of industry globalization. Whilst previous single country studies of strategic decision making have highlighted the effect of variables such as uncertainty, environmental stability, competition intensity and organizational position, we argue that diverse national values are also critical, albeit tempered by convergence pressures arising from globalization. Our incipient model, recognizing rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 72 publications
2
19
0
Order By: Relevance
“…Cross-country research suggests that these differences may be associated with the national context (Carr and Harris, 2004;Carr andTomkins, 1996, 1998;Jones et al, 1993;Shields et al, 1991). Additionally, documented differences in the emphasis on strategic versus financial considerations among companies from the same country contexts suggest that these differences may be associated with other contextual variables, as well (e.g.…”
Section: Introductionmentioning
confidence: 88%
“…Cross-country research suggests that these differences may be associated with the national context (Carr and Harris, 2004;Carr andTomkins, 1996, 1998;Jones et al, 1993;Shields et al, 1991). Additionally, documented differences in the emphasis on strategic versus financial considerations among companies from the same country contexts suggest that these differences may be associated with other contextual variables, as well (e.g.…”
Section: Introductionmentioning
confidence: 88%
“…However, while investment decisions may be financial decisions, there is a growing recognition that they are also often non-financially based decisions. Nevertheless, studies have mainly considered on only the impact of national context (e.g., Carr & Harris, 2004;Carr & Tomkins, 1996, 1998Shields, Chow, Kato, & Nakagawa, 1991), with little evidence provided regarding which contextual variables, other than country 1 For the purposes of this study the relative degree of emphasis decision-makers attach to a financial and nonfinancial orientation in capital budgeting can be interpreted as either purposeful emphasis or decision-makers may unconsciously attach emphasis. 2 A substantial literature exists on the agency problem and the associated goal incongruence between principals and agents (see e.g., Baiman, 1990;Berle & Means, 1932;Fama, 1980;Jensen & Meckling, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…Different national cultures exhibit different approaches to decision making (Hofstede, 1994, 2001, Child 1981). Carr and Harris (2004), when comparing the strategic investment decision style of companies from Germany, Britain, Japan, and the US, in the automotive component business, concluded that divergence in national values had a significant impact on investment decision style. For example: the German emphasis on a small top professional team; the extensiveness of consultation practices in Japan; the surprisingly systematic approach in the US; and the pragmatic, shallower approach of the British.…”
Section: Introductionmentioning
confidence: 99%